VALERIANA MOYANOI SPEG. (VALERIANACEAE), NUEVO REGISTRO PARA LA FLORA DE CHILE - Saldivia, Patricio; Rojas, Gloria (Gayana Botánica, 2006)
Valeriana moyanoi Speg. (Valerianaceae), known until today just for the Argentinean flora, was collected for the first time in Chile in two places of the XI Region of Aysén; Cerro Rosado and the Jeinimeni Lake National Reserve. This study includes a description of the species, its Chilean-Argentinean distribution, habitat and associate species.